Protocol for a prospective, longitudinal, cohort study of recovery pathways, acute biomarkers and cost for children with persistent postconcussion symptoms: the Take CARe Biomarkers study. Issue 2 (24th February 2019) - Takagi, Michael; Babl, Franz E; Anderson, Nicholas; Bressan, Silvia; Clarke, Cathriona J; Crichton, Ali; Dalziel, Kim; Davis, Gavin A; Doyle, Melissa; Dunne, Kevin; Godfrey, Celia; Hearps, Stephen J C; et al.
Abstract : Introduction: The majority of children who sustain a concussion will recover quickly, but a significant minority will experience ongoing postconcussive symptoms, known as postconcussion syndrome (PCS). These symptoms include emotional, behavioural, cognitive and physical symptoms and can lead to considerable disability. The neurobiological underpinnings of PCS are poorly understood, limiting potential clinical interventions. As such, patients and families frequently re-present to clinical services, who are often ill equipped to address the multifactorial nature of PCS. This contributes to the high cost of concussion management and the disability of children experiencing PCS. The aims of the present study are: (1) to plot and contrast recovery pathways for children with concussion from time of injury to 3 months postinjury, (ii) evaluate the contribution of acute biomarkers (ie, blood, MRI) to delayed recovery postconcussion and (3) estimate financial costs of child concussion to patients attending the emergency department (ED) of a tertiary children's hospital and factors predicting high cost. Methods and analysis: Take C.A.Re is a prospective, longitudinal study at a tertiary children's hospital, recruiting and assessing 525 patients aged 5–<18 years (400 concussion, 125 orthopaedic injury) who present to the ED with a concussion and following them at 1–4 days, 2 weeks, 1 month and 3 months postinjury. Multiple domains are assessed: preinjury and postinjury, clinical, MRI, blood samples, neuropsychological, psychological and economic. PCS is defined as the presence of ≥2 symptoms on the Post Concussive Symptoms Inventory rated as worse compared with baseline 1 month postinjury. Main analyses comprise longitudinal Generalised Estimating Equation models and regression analyses of predictors of recovery and factors predicting high economic costs. Ethics and dissemination: Ethical approval has been obtained through the Royal Children's Hospital Melbourne Human Research Ethics Committee (33122). We aim to disseminate the findings through international conferences, international peer-reviewed journals and social media. Trial registration number: ACTRN12615000316505; Results.